Kinesio taping reduces elbow pain during resisted wrist extension in patients with chronic lateral epicondylitis: a randomized, double-blinded, cross-over study - Yen-Ting Cho; Wen-Yen Hsu; Li-Fong Lin; Yen-Nung Lin (BMC Musculoskeletal Disorders, 2018)
Abstract Background Lateral epicondylitis is frequently seen in racquet sport players and the treatments are usually symptomatic rather than curative. Taping therapy is cheap and easy to apply in the sport field. In this study we valued the effectiveness of Kinesio taping (KT) on immediate pain control for patients with chronic lateral epicondylitis. Methods We conducted a randomized, double-blinded, cross-over study with 15 patients with chronic lateral epicondylitis. All participants received two taping sessions in a random order with a 3-day interval in between: one with KT and the other with sham taping (ST). Pain perceived during resisted wrist extension and at rest using numeric rating scale (NRS), the pain-free grip strength, and the pressure pain threshold, were measured before and 15 min after the tape was applied. Results A significant reduction of 2.1 ± 1.6 (Z = − 3.081, P = 0.002) and 0.7 ± 0.8 (Z = − 2.428, P = 0.015) was found on a NRS with KT and ST, respectively, indicating that both taping sessions produced immediate pain relief for resisted wrist extension. Both taping sessions significantly improved the pain-free grip strength with increases of 3.31 ± 5.05 (Z = − 2.615, P = 0.009) and 2.43 ± 3.31 (Z = − 2.783, P = 0.005) kg found with KT and ST, respectively. Compared with ST, KT exhibited superiority in controlling pain experienced during resisted wrist extension (Z = − 2.168, P = 0.030). Conclusions Taping produced unneglectable placebo effects on pain relief and painf-free grip strength for patients with lateral epicondylitis, and KT seemed to have additional effects on controlling pain that was elicited by resisted wrist extension. Trial registration ISRCTN13618356 (retrospectively registered on 13/02/2017).